The effect of demographic and academic backgrounds on financial accounting performance - Wan Abdullah, Wan Faizah; Abu Bakar, Siti Salmah; Marzuki, Marzlin; Abdul Rahim, Noraini; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
The main objective of this study is to compare the Financial Accounting performance between students with and without Sijil Pelajaran Malaysia grades and their demographic background. The study was carried out among the Diploma in Accountancy students at Universiti Teknologi MARA Kedah campus. 190 usable data were obtained from the Academic Affairs Department at the campus. Independent t-test was used to analyse the data. The finding shows that the performance of students with SPM Accounting is significantly higher for FAR 100 and FAR 200. The same result is true for those with SPM Commerce on FAR 100. On the other hand, there is no significant difference between those with and without SPM Additional Mathematics and SPM Economics performances in all Financial Accounting courses. In terms of gender, females performed significantly better in FAR 200 only. For school location, there is no difference between students from urban and rural schools on the performance of Financial Accounting.